2015
DOI: 10.2147/ndt.s87118
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of complicated grief among individuals with acute coronary syndromes

Abstract: ObjectiveThe study aimed at exploring bereavement and complicated grief (CG) symptoms among subjects without a history of coronary heart disease (CHD) at the time of a first acute coronary syndrome (ACS) and to evaluate the relationship of CG symptoms and ACS.MethodOverall, 149 subjects with ACS (namely, acute myocardial infarct with or without ST-segment elevation or unstable angina), with no previous history of CHD, admitted to three cardiac intensive care units were included and evaluated by the Structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Complicated grief where the patient may be confused about his identity, role socially, there are changes, responses and even depression that may be related with physiological changes such as increased heart rate or blood pressure, Increasing cortisol levels, sleep disorders and changes in the immune system body (Buckley et al, 2012;Shear, 2015). Complicated grief according to Pini, Gesi, Abelli, Cardini, Lari, Felice, ... & Borelli (2015) related to the incident coronary heart disease. Pini et al found in 149 subjects with the disease coronary heart disease, as many as 118 (79.2%) improve complicated grief.…”
Section: Discussionmentioning
confidence: 99%
“…Complicated grief where the patient may be confused about his identity, role socially, there are changes, responses and even depression that may be related with physiological changes such as increased heart rate or blood pressure, Increasing cortisol levels, sleep disorders and changes in the immune system body (Buckley et al, 2012;Shear, 2015). Complicated grief according to Pini, Gesi, Abelli, Cardini, Lari, Felice, ... & Borelli (2015) related to the incident coronary heart disease. Pini et al found in 149 subjects with the disease coronary heart disease, as many as 118 (79.2%) improve complicated grief.…”
Section: Discussionmentioning
confidence: 99%
“…Higher prevalence rates are associated with unnatural losses, with nearly half of such bereaved individuals experiencing PGD (Djelantik et al, 2020), and almost a quarter of parents who lost a child experiencing it (Kersting et al, 2011). PGDhas been shown to be distinct from depression and post‐traumatic stress disorder (PTSD) (Boelen & van den Bout, 2005; Cozza et al (2016); Jordan & Litz, 2014; Maciejewski et al, 2016; Prigerson et al, 2021) and to uniquely predict poor mental and physical health outcomes (Latham & Prigerson, 2011; Pini et al, 2015; Prigerson et al, 2008; Stroebe et al, 2013). Despite the distinction between disorders, results from some randomized clinical trials (RCTs) and a recent meta‐analysis have shown that PGD shares high comorbidity with major depressive disorder, PTSD, and/or depressive, anxiety, and post‐traumatic stress symptoms as secondary outcomes (Bryant et al, 2014; Eisma et al, 2015; Komischke‐Konnerup et al, 2021; Lenferink et al, 2017; Papa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“… 23 26 However, only two previous studies have indicated an association between poor self-reported health in caregivers and PGD. 18 , 27 Both studies were cross-sectional and conducted after bereavement; one assessed health status before bereavement in a retrospective study design, whereas the other only examined health status after bereavement. Hence, a prospective study investigating whether caregivers’ health status during caregiving is a predictor of PGD could increase knowledge in this area and support prevention.…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to describe the physical and mental health status in caregivers of patients at the end of life and to investigate whether health status may predict PGD. Based on previous research, 18,27 we hypothesised to find an association between poor physical and mental health in caregivers before bereavement and development of PGD after bereavement.…”
Section: Introductionmentioning
confidence: 99%